People living with HIV in Ogun East Senatorial district, Nigeria-a happy and physically active people - Olumide Abiodun; Chikwendu Amaike; Chibuike A. Oguine; Opeoluwa Ogundipe; Ebunoluwa Afolabi; Aanuoluwa A. Afolabi; Olabisi T. Bamidele (Elsevier, 2024)
Background: Physically active individuals tend to be happy people. This study aimed to assess the relationship between physical activity and happiness among people living with HIV. Methods: We conducted a cross-sectional survey of 412 HIV-positive participants and obtained data using an interviewer-based questionnaire that included sociodemographic questions, extracts from SF-36 to assess happiness and the International Physical Activity Questionnaire-Short form (IPAQ-SF) to assess the intensity and domains of physical activity. We derived the proportions and means (and standard deviation) of participants' characteristics and disaggregated the factors by reported happiness. Subsequently, we conducted bivariate and binary logistic analyses to assess the associations of happiness with physical activity volume, intensity and domains. Statistical significance was set at 5%. Results: Participants were predominantly females (68.4%) with a mean age of 47.4 (±10.3). Most (372; 90.3%) participants reported feeling happy in the preceding month. The prevalence of physical activity volume was 18.7% (low), 40.5% (moderate) and 40.8% (high), respectively. Physical activity level was related to happiness as 97.6% of the study participants who reported a high level of physical activity also reported feeling happy (ꭓ2 = 30.009; p = <0.001). The study found a positive dose-response association between the volume, intensity, and domains of physical activity and happiness (p < 0.05). Conclusion: Our study has demonstrated that HIV participants who engage themselves in physical activity are happy people. The findings may aid policy formulation aimed at physical activity interventions for promoting happiness and other positive mental health constructs among people living with HIV.